A Multilevel Approach to Understanding the Determinants of Maternal Harsh Parenting: the Importance of Maternal Age and Perceived Partner Support. - Farley, Laura; Oliver, Bonamy R.; Pike, Alison (Journal of Child & Family Studies, 2021)
Determinants of parenting are most often considered using one child per family within a cross-sectional design. In 182 families, the current study included two siblings and sought to predict maternal harsh parenting measured prospectively when each child was age 2 years from child gender, infant temperament, maternal age, maternal educational attainment, maternal depression and anxiety and maternal perceptions of partner support. Multilevel modeling was used to examine between- and within-family variance simultaneously. Mothers reported levels of harsh parenting that were similar towards both children (intraclass correlation = 0.69). Thus, the majority of variance in maternal perceptions of their harsh parenting resided between rather than within families and was accounted for in part by maternal age and maternal perceptions of partner support. Results are discussed in relation to family-wide determinants of harsh parenting, previous literature pertaining to parenting siblings and the potential avenues for future research and practice. Highlights: Determinants of harsh parenting examined within a prospective, longitudinal sibling study. Multilevel design for simultaneous consideration of child-specific and family-wide predictors. Family-wide determinants were dominant, over and above child characteristics. Implications of perceptions of partner support discussed. Importance of considering parenting determinants within a sibling design emphasized.